DO PLANO NACIONAL DE POLÍTICAS PARA AS MULHERES AO ¨MACHISTÉRIO¨ DE TEMER - Renata Gonçalves (Universidade Federal do Maranhão, 2018)
This article discusses the trajectory of feminist and women’s struggles, whi- ch culminated in the creation of the Special Secretariat for Women’s Policies (SWP) and the National Plan for Women’s Policies (NPWP), which sought to ensure a gender perspective in the transversality of all instances and institutio- nal competences, technical-administrative of governability of the Brazilian Sta- te. These policies were hit hard by the cuts made by Michel Temer government.